Inequality and violent crime: evidence from data on robbery and violent theft - Neumayer, Eric (Journal of peace research, 2004)
This article argues that the link between income inequality and violent property crime might be spurious, complementing a similar argument in prior analysis by the author on the determinants of homicide. In contrast, Fajnzylber, Lederman & Loayza (1998; 2002a, b) provide seemingly strong and robust evidence that inequality causes a higher rate of both homicide and robbery/violent theft even after controlling for country-specific fixed effects. Our results suggest that inequality is not a statistically significant determinant, unless either country-specific effects are not controlled for or the sample is artificially restricted to a small number of countries. The reason why the link between inequality and violent property crime might be spurious is that income inequality is likely to be strongly correlated with country-specific fixed effects such as cultural differences. A high degree of inequality might be socially undesirable for any number of reasons, but that it causes violent crime is far from proven